Heart failure and chronic obstructive airway disease as combined comorbidities. Meta-analysis and Review - Hadi AR Hadi Khafaji; Jassim Al Suwaidi; Asim Cheema (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2019)
Background: The existence of COPD and heart failure in elderly population adds additional morbidity and mortality risk than if those with only one of the two comorbidities. The aim of the current metaanalysis was to explore the effect of COPD on heart failure patient in terms of all-cause mortality, cardiac mortality and recurrent heart failure hospitalization. Methods and results: A comprehensive search of PubMed, MEDLINE, Embase and Cochrane was conducted until August 2017. The total standardized mean difference, with 95% (CI), was estimated for  fixed and random effects models to present "pooled effect" for continuous outcomes (mean ± standard deviation or median ± interquartile range) & categorical outcomes (Odds risk OR). Statistical heterogeneity among studies was assessed with Cochran's Q test and the I2 statistic.